High-Efficient G2V Battery Charger for 48V Local e-Transportation - Dixit A.; Pande K.; Rathore A.K.; Singh R.K.; Mishra S.K. (My University, 2025)
This paper proposes a low-cost high efficiency two stage battery charger where the first stage is a discontinuous current mode (DCM) based two-cell buck-boost converter for power factor correction (PFC) whereas the second stage is an unregulated half-bridge LLC resonant converter which provides isolation as well as soft-switching for primary switches. Synchronous Rectification (SR) on transformer secondary is used to improve converter efficiency. The proposed charger not only provides isolation but also reduces the control burden and cost, by reducing number of sensors. A detailed design and loss analysis is done in order to obtain the optimum DC-Link voltage for the proposed battery charger. To verify the design, Simulation and hardware results are presented which confirms the design and analysis. © 2020 IEEE.